50 years field oriented control of three-phase AC drives in the practice - the state-of-the-art - Quang, Nguyen Phung (Journal of Computer Science and Cybernetics, 2024)
From DC motors (DCM) we know, it is possible to independently control the two currents of the flux and torque generating. Because the two DCM circuits are completely isolated, we obtain simple adjustment algorithms that require little computing time on the microprocessor. For this reason, DCM has been at the forefront of the application of digital controls in drive control systems in the early years, especially in high-performance systems. On the contrary, the three-phase AC motor (ACM) has a complex structure due to the winding system and three-phase power supply, and has caused significant difficulties in the mathematical description of the above decoupling characteristics. The purpose of the field-oriented control (FOC) is therefore to create a tool that allows the decoupling control of the flux and torque-producing current components from the three-phase AC currents flowing in the coil. The FOC drive system is a system based on the principle of decoupling the above power components thanks to the stator current feedback control (the innermost circuit of the drive system). The FOC-type control method belongs to the class of vector control methods for electrical machines. On the occasion of the 50th anniversary of FOC, this paper aims to provide an overview of the development status of FOC in industrial practice. The content presented deals mainly with 3-phase induction motors.